Coping experiences of Pakistani nurses against corona stressor; a qualitative study - H. Haider, Ali (International Journal of Advanced Nursing Studies, 2020)
Objective: The aim of the present qualitative study was to find out how Pakistani Nurses are experiencing the coping strategies against Corona- Stressor.Background: Corona is the World- Wide stressor for Nurses. The Pakistani Nurses are experiencing this stressor and are coping with it too. The present study is on Coping of Nurses of Pakistan against Corona- Stressor.Method: Narrative variation of qualitative research with conventional content analysis was applied to extract results from open- ended interview questions which were administered on nurses face to face with purposive sampling technique.Results: Six major themes; five of conventional coping strategies and one new coping strategy were used by Nurses against Corona- Stressor.Discussion & Conclusion: Nurses in Pakistan are using Standard Operating Procedures as a new coping strategy against Corona Stressor with the already established conventional coping strategies.Â Â Â